New user? Sign up

Existing user? Sign in

If (x - 2)^(x^2 - 9)^(x^2 - 4) = 1.

Find the sum of all values of x.

Note by Dev Sharma 2 years, 1 month ago

Sort by:

Is the answer 3+(-3) =0?

Because to get zero either x-2 = 1 or x^2-9 = 0.

So, x = 3 gives 1^0^5 = 1. and x = -3 gives -5^0^5 = 1.

Log in to reply

possible x are -3 and 3 so .. -3+3=0

3 or -3

Answer is 0.

Problem Loading...

Note Loading...

Set Loading...

## Comments

Sort by:

TopNewestIs the answer 3+(-3) =0?

Because to get zero either x-2 = 1 or x^2-9 = 0.

So, x = 3 gives 1^0^5 = 1. and x = -3 gives -5^0^5 = 1.

Log in to reply

possible x are -3 and 3 so .. -3+3=0

Log in to reply

3 or -3

Log in to reply

Answer is 0.

Log in to reply